Evaluasi Kualitas Pelaksanaan Mata Kuliah Riset Agroindustri dengan Metode Focused Quality - Rahayu, Hilda Putri; Sugiarti, Yatti (Program Studi Pendidikan Teknologi Agroindustri, UPI (Universitas Pendidikan Indonesia))
Agro-Industry Research course is one of the compulsory subjects which included in the category of core subjects Study Program are weighted 4 credits and as one of the requirements to obtain a Bachelor's degree. Indicator of achievement of this course is students are able to write a scientific paper with analysis based on research results conducted during the research course. Based on the preliminary survey results, it was known that there are some things that become obstacles in the implementation of agro-industry research course, so it needs to be improved. The purpose of this study was to determine implementation quality of agroindustry research course and provide recommendations in order to improve the quality. This research method was quality focused method. This method was used to determine students expectation, to improve the quality of agro-industry research course. There are six steps being taken in this method, including the preparation of key processes, the preparation of a critical success factor, the calculation of the amount of impact, performance calculation process, the performance gap calculation process, the calculation of the weighted gaps, prioritization and manufacture a priority matrix. The result showed implementation quality of agro-industry research course was fairly good quality. Improving the quality of the implementation can be done by doing the appropriate repair priorities and strategies for improvement.Â